Peripheral osteoma of the nasal bone after laser treatment: A case report - Hwang, Jae ha (Medicine (Baltimore), 2019)
INTRODUCTION: Peripheral osteoma, which arises from the periosteum, commonly develops in the head and neck region and is found frequently in the mandible, maxilla, and paranasal sinuses. However, osteoma of the face, especially from the nasal bone, is quite rare. PATIENT CONCERNS: A 34-year-old female visited our outpatient department with a small mass on the nose. She had n laser treatment of nevus at the same spot 14 years before, and it had enlarged slowly since 10 years before. DIAGOSIS: Computed tomography scan revealed a 0.7 × 0.5 cm sized radio-opaque tumor of the nasal bone. INTERVENTIONS: Under general anesthesia, surgical excision was performed through a transcolumellar and infracartilaginous incision. The excised tumor was a 0.7 × 0.5 cm sized hard mass. OUTCOMES: Biopsy confirmed it as a peripheral osteoma. After tumor removal, structural stability of nasal framework including bone and cartilage was maintained, and symmetry of the nasal dorsum was acquired. CONCLUSION: Chronic osteoma can compress the abutting structures. In the case of the nose, either structural instability or asymmetry can occur. By applying open rhinoplasty techniques, postoperative scars could be hidden and additional correction of the affected structure could be carried out if necessary. As a result, the surgeon can achieve the functional and esthetic outcomes simultaneously.